Rb and Cs doping effects in sodium borohydride: Density functional theory for hydrogen (H2) storage purpose. (6th January 2021) - Makhdoom, Madiha; Azam, Sikander; Alrebdi, Tahani A.; Khan, Saleem Ayaz; Iqbal, Azhar; Kanoun, Mohammed Benali; Goumri-Said, Souraya
Abstract: Fuel cell technology based on stationary and mobile applications is needing new hydrogen storage materials equipped with huge gravimetric and volumetric hydrogen densities. Examining the fundamental properties of hydrides is an important part of such process, mainly to understand the structure change's impact on the hydrogen storage. Herein, we applied ab-initio density functional theory using full potential linear augmented plane method to explore the effect of rubidium and cesium doping in sodium borohydride, NaBH4 . The electronic structure calculations exposed the semiconducting nature of NaBH4 and derived doped structures NaRbBH4 and NaCsBH4 . The hydrogen (H2 ) storage capacity is found 10.66 wt %, 3.27 wt % and 2.36 wt % within a reasonable free energy of −28.514 kJ/mol, −29.709 kJ, −28.51 kJ/mol for NaBH4, NaRbBH4 and NaCsBH4 respectively from quasi-harmonic approximation. Also, we extracted the heat capacity and Debye temperature from vibrational analysis based on phonon calculation. The discovered features show the potential use of presented sodium borohydrides for practical H2 storage devices. Graphical abstract: Image 1 Highlights: Fundamental properties of hydrides for fuel cell technology is explored. The structure change's impact on the hydrogen storage is investigated. DFT and DFPT approaches were used to the effect of Rb/Cs doping in NaBH4 . H2 storage capacity was evaluated in all compounds as 10.66 wt %, 3.27 wt % and 2.36 wt %. Heat capacity and Debye temperature were computed from vibrational analysis and phonon.